Nano-mineralogy and growth environment of Fe-Mn polymetallic crusts and nodules from the South China Sea - Ren, Yingzhi; Guan, Yao; Sun, Xiaoming; Xu, Li; Xiao, Zhenglian; Deng, Yuqi; He, Wentao (Frontiers in Marine Science, 2023)
Fe-Mn polymetallic crusts and nodules from the South China Sea (SCS) consist of submarine ferromanganese (Fe-Mn) oxide precipitates, and represent important marine mineral resource with substantial economic and scientific research value. Previous studies on the SCS polymetallic crusts and nodules were mainly focused on their bulk mineralogy and geochemistry, whilst research on their nanomineralogy is still lacking. In this study, transmission electron microscopy (TEM), Raman spectroscopic mapping, and in-situ micro X-ray diffraction (XRD) analysis were conducted on the nano-mineralogy of the SCS polymetallic crusts and nodules. It is found that the SCS polymetallic crusts and nodules consist mainly of layered/columnar/mottled nano-phase Fe-Mn minerals and detritus such as quartz, feldspar, and clays. Also, an independent Ti mineral phase has been documented, and the mineralogical analysis reveals the transformation from vernadite to birnessite and todorokite. Titanium forms colloidal minerals in seawater and precipitates into the crusts and nodules with other colloids, such as FeOOH and Si-Al. Vernadite and birnessite can be transformed to todorokite with stable structure under sub-oxic conditions. Therefore, the SCS polymetallic crusts and nodules were formed in a short period of sub-oxic environment and diagenetic process, and the transformation can influence the enrichment of Ni and other metals during the crust/nodule growth.